2003
DOI: 10.1046/j.1462-2920.2003.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Salmonella Enteritidis Phage Type 4 in the environment and arthropod vectors on an empty free‐range chicken farm

Abstract: The persistence of S. Enteritidis PT4 was studied on a free-range breeding chicken farm which had been depopulated following identification of the organism in breeding birds. The site was sampled periodically for 26 months after depopulation and the organism was found to persist in litter, dried faeces and feed, but not in dust within empty poultry houses, for the whole of that period. Salmonella Enteritidis PT4 was also found in soil samples after 8 months but not 13 months and in faeces from wild mice, foxes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 40 publications
0
55
0
1
Order By: Relevance
“…A need for coordination of subpopulations with specialized virulence functions provides a framework for understanding how S. enterica serovar Enteritidis can be prevalent in the poultry environment without resulting in egg contamination, why some vector hosts contribute more than others to highincidence egg contamination, and why outbreaks occur sporadically (8,34).…”
Section: Discussionmentioning
confidence: 99%
“…A need for coordination of subpopulations with specialized virulence functions provides a framework for understanding how S. enterica serovar Enteritidis can be prevalent in the poultry environment without resulting in egg contamination, why some vector hosts contribute more than others to highincidence egg contamination, and why outbreaks occur sporadically (8,34).…”
Section: Discussionmentioning
confidence: 99%
“…There is a correlation between the presence of Salmonella in mice and the contamination of poultry. Moreover, some recent reports have shown that several wildlife species, especially rodents, are involved in the maintenance of S. Enteritidis infection on farms [38,52,86]. It is unlikely, however, that there is a causal link between the use of S. Enteritidis as rodenticide and the human cases reported since 1960 [61,129].…”
Section: Rodent Reservoirmentioning
confidence: 99%
“…However, the direct application of this waste material to agricultural land can be harmful to the environment due to nutrient and pathogenic microorganisms in runoff (14,29). Salmonella-contaminated litter can be a potential source of produce contamination in the agricultural field due to the prolonged survival of Salmonella in the environment (9,17). Heat treatments are usually recommended to reduce or eliminate potential pathogenic microorganisms in animal wastes.…”
mentioning
confidence: 99%